Feeling difference: history, encounter and the affective life of a postcolonial neighbourhood - Meer,Talia (Department of Sociology, 2022)
In this dissertation I develop an account of Observatory, a neighbourhood of Cape Town, South Africa, and its fem (cis- and transwomen, feminine men and gender non-conforming) residents, to show how place history, personal identity and everyday encounters come to be co-constituted through affect. I argue that structures of feeling - overarching historical affects - and the feeling of structures - embodied experiences of historical affects and structures of difference, including race, class and gender - shape life over the long durée and in the immediacy of encounters. As different but connected affective scales they elucidate how fems, usually cast as subjugated in urban life, are implicated in the unfolding of history, how they accomplish specific trajectories, and unexpectedly summon the past or future through embodied encounters. Through intimate, visceral, but deeply social and historical ways of knowing their own bodies and others, fems feel out, enact and make differences daily. These differences are constructed relationally, not just hierarchically, as identities and histories are reconstituted and power geometries shift from encounter to encounter. This dissertation is purposefully transdisciplinary and seeks an intersectional sociological understanding of embodied affect through an expansive view of the gender-based violence literature, urban and diversity studies, and critical race and queer theory. It combines exploratory archival work, in-depth interviews with twenty fems, and ethnographic observation to produce a historically grounded and empirically rich take on the relationship between urban space, postcolonial time, and everyday forms of difference, embodiment and encounter. In doing so, it straddles a concern for how fems make liveable lives in contexts of gendered insecurity, but also for how their strategies may in turn operationalise other historically entrenched forms of difference, particularly race, thus constructing and endangering others. In this dissertation, I re-illuminate a familiar, although underexplored, race-gender-space encounter. I denaturalise not only the white, global north ciswoman as the focus of inquiry into gendered city life, but also her presumed position of oppression. By addressing a range of fem positionalities in Observatory, I argue instead that fems can and do access histories of power, shaped by colonialism and apartheid. This highlights fem capacity to effect and affect urban space and those within. In addition, I develop an empirical ground for the study of affect that attends to life as lived and emplaced, and that provides an analysis of postcolonial affects from the global south. In this way I push beyond narrow developmentalist approaches to global south cities to bring their rich affective life into focus.